2009
DOI: 10.1007/s11673-009-9186-x
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Research: A Commitment to Walking the Talk. The Gudaga Study—an Australian Case Study

Abstract: Increasingly, the role of health research in improving the discrepancies in health outcomes between Indigenous and non-Indigenous populations in developed countries is being recognised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…There are a few examples of others [5][6][7][8] who have documented research according to Values and ethics. Interestingly, these examples identify relationships and partnerships as important facilitators to their research, echoing the processes identified in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few examples of others [5][6][7][8] who have documented research according to Values and ethics. Interestingly, these examples identify relationships and partnerships as important facilitators to their research, echoing the processes identified in this review.…”
Section: Discussionmentioning
confidence: 99%
“…For research involving Indigenous people, Values and ethics has the same status and authority as the National statement on ethical conduct in human research. 4 Although some authors have described addressing the Values and ethics document during research [5][6][7][8] , its impact on research conduct is unclear. 5,9 An evaluation of Values and ethics is under way.…”
Section: To Guide Researchers Ethics Committees and Communities Valmentioning
confidence: 99%
“…The Study has also taken the values and ethics recommended by the NHMRC 11 and developed a strong theoretical framework that underpins the establishment and implementation of the research. 48 It is anticipated that the theoretical framework and implementation of the protocols will provide robust data on the health, development and health services use of urban Aboriginal infants and children on the eastern seaboard of Australia.…”
Section: Mothers Of Aboriginal Infants Identified Through Other Netwomentioning
confidence: 99%
“…Examples of community-controlled research [ 16 ], community participation in research [ 17 ], documentation of Local Protocols [ 18 , 19 ], a description of important principles for research [ 20 ] and recommendations for completing specific research methods with Indigenous communities, for example conducting survey-based research [ 8 ], have been published. However, there are few examples specific actions taken by researchers to address Values and Ethics [ 9 ] when conducting health research [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%